OLD RUSSIAN SUBORDINATE CLAUSE WITH A PARTICIPLE AS THE ONLY PREDICATIVE: A DIACHRONIC ASPECT - Boris V. Kunavin (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article investigates complex sentences, in the subordinate part of which the nominal active participle is the only predicative. Its relevance is expressed in the great importance of these constructions, in understanding the originality of Old Russian syntax in general and the features of the evolution of the syntactic functions of nominal active participles on the way of their transformation into gerunds in particular, and in the inconsistency of linguistic interpretation of their structure, functions, and genesis by various researchers. The study aims at providing comprehensive description of syntactic constructions with a nominal active participle as the only predicative and determination of the dynamics of their use throughout the history of the Russian language, starting with the written tradition up to the 18th century. To achieve the goal, descriptive, comparative-historical, and comparative-typological methods were applied to the analysis of literary texts of the 11th – 17th centuries, which enabled the identification of various conjunctions and connective words, used to provide joining a subordinate clause to the main part of the sentences under study. The types of participial clauses were identified; the reasons for their distribution in the Old Russian language were established, their originality was proved; the genesis, genre and stylistic marking, the reasons for the loss were determined, amid the elimination of simple preterit forms, the development of hypotaxis and the structure of a simple sentence.